PROTECTING MENTAL HEALTH IN DIGITAL EDUCATION: INTERNATIONAL EXPERIENCE AND NEW APPROACHES (Universal International Scientific Journal, 2026)
The rapid digitalization of education has significantly changed teaching and learning processes around the world. While digital technologies have created new opportunities for access to information, flexible learning environments, and international academic collaboration, they have also created new psychological challenges for students and teachers. Therefore, protecting mental health in digital learning environments has become a key issue in modern educational policy and academic research. This article analyzes international experiences and innovative approaches to supporting psychological well-being in digital learning environments.Keywords: digital learning, mental health, psychological well-being, higher education, digital learning environments, innovative approaches
Keywords: digital learning environment, mental health, psychological well-being, online education, stress and anxiety, cybersecurity, digital hygiene, student health, pedagogical support, international experience, innovative approaches, distance learning, emotional intelligence, psychological services, educational technologies, artificial intelligence and education, social adaptation, mental prevention, inclusiveness in education, prosperous learning environment.